Eficiência agronômica de fosfatos de rocha, via adubação corretiva, em um cambissolo cultivado com milho no Estado de Sergipe - Souza, Richard Matos de (2013)
In the last decade, the adoption of technologies in corn crop provided a significant productivity and yield increase in Sergipe State, Brazil. In this state, soils classified as Inceptisols are very adequate for corn cropping. The only limitation presented by those soils is the low levels of available P for plants. Fertilization to increase soil P level through rock phosphates should be considered in order to increase P response to annual P fertilization in the row, which is related to the crop requirement. On the other hand, direct application of rock phosphates in soils which have pH (H2O) above 5,5 and a high calcium content, like those above mentioned, has not been recommended because they could slow down the dissolution of rock phosphates. A strip split plot in a complete randomized blocks design with four replications experiment, was set up in order to study the agronomic effectiveness of Bayóvar and Itafós rock phosphates applied for soil P correction in an Inceptisol with pH 6,0 and high calcium content. Rock phosphates and triple superphosphate, used as a reference source, were broadcasted in the main plots and incorporated by disk plowing. A main plot without soil P correction also was included in the study. In the subplots annual P application at rates of 0, 60 e 120 kg.ha-1 as triple superphosphate were accomplished in the planting rows. Corn was grown in the raining seasons of 2011 and 2012. Yield and P leaf content indicated that less P from annual application was needed in treatments corrected by those sources with higher P solubility. Mehlich-1 and mixed resin method removed more soil P from rock phosphates plots than the reference TSP plot. The relative agronomic effectiveness (RAE) of Bayóvar and Itafós rock phosphates were 77,19% and 45,66%, respectively, calculated based on two years.